2018
DOI: 10.1186/s13027-018-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with HBV-related hepatocellular carcinoma following hepatic resection

Abstract: BackgroundTo analyze prognostic factors following hepatic resection in patients with HBV-related hepatocellular carcinoma.MethodsWe retrospectively analyzed 217 patients with HBV-related hepatocellular carcinoma who underwent hepatic resection at our hospital between January 2006 and December 2015. Disease-free survival and overall survival rates were analyzed using the Kaplan–Meier method and the log-rank test. The association between recurrence and survival and various clinicopathological factors, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…According to the data shown in Table 1, 5 studies reported post‐treatment death rates in HCC patients with versus without APT 30–34 . These studies included 3281 patients, with 930 (29.9%) deaths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data shown in Table 1, 5 studies reported post‐treatment death rates in HCC patients with versus without APT 30–34 . These studies included 3281 patients, with 930 (29.9%) deaths.…”
Section: Resultsmentioning
confidence: 99%
“…| RESULTS3.1 | Search results and study characteristicsThe PRISMA flow diagram depicts the article selection process (Figure1). Briefly, among the 493 articles screened, 156 articles were assessed for eligibility with 20 studies, 15 on HCC incidence and five on mortality outcome following treatment, which were finally included in the meta-analysis [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. …”
mentioning
confidence: 99%
“…Indeed, independent prognostic factors vary significantly in identical disease and treatment settings at different hospitals. For example, numerous studies have reported that tumor size, which is commonly involved in staging systems for HCC, is not an independent prognostic factor for HCC after resection (16,17). Therefore, considering disparities in prognostic factors influenced by external factors, the performance of a model is likely to be most effective in the center from which the model was derived.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 5083 patients from the 11 retrospective cohort studies were included in this study (12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23). The level of evidence was 2a.…”
Section: Characteristics Of the Selected Articlesmentioning
confidence: 99%
“…( 14 ) and Rungsakulkij et al . ( 15 ), there are no obvious connections between patient outcomes and NLR or PLR levels.…”
Section: Introductionmentioning
confidence: 99%